(untitled) (Mustansiria Dental Journal, 2019)
Background: Soft lining materials play an important role in modern prosthodontics treatment because of their capability to restore the inflamed and distorted mucosa. The purpose of the research was to estimate the influence of acrylic denture base reinforcement with silanted nano fillers (Al2O3 and Sio2) separately on tensile and shear bond strength of soft lining material and studying effect of thermo cycling on bonding strength. Materials and methods: Total 120 specimens were prepared; it divided into 60 Specimens for shear bond strength test and 6o specimens for tensile bond strength test. Specimens were sub grouped into 30 Specimens without thermo cycling and 30 specimens with thermo cycling. Each sub group is consisted from: 10 Specimens control, 10 specimens were reinforced with 2 wt% of Al2O3 nano fillers and 10 specimens were reinforced with 5 wt% of SiO2 nano fillers. Samples were processed depending on test applied. Soft lining material was applied for each testing group. Samples were immersed in distal water for 24 hours at 37°C before testing. For thermo cycling test, specimen were thermo cycled in thermo cycling device. Bonding strength test was done using INSTRON universal testing machine. Results: reinforcement of acrylic denture base with nano-fillers was significantly increase both tensile and shear bonding of lining material and thermo cycling decreases both bonding strength. Conclusion: reinforcement of acrylic denture base with nano fillers could improve bonding strength of lining material, while thermo cycling had a deleterious effect on bonding strength.